The rights (and responsibilities) of the public to advance health through research - Fabrice Jotterand; Ryan Spellecy; Reza Shaker (BMC, 2021)
Abstract In this commentary we assert that the rights and responsibilities of the community at large as an important key stakeholder in the effort of advancing health through research and discovery have not been carefully examined and delineated. The time has come to investigate the nature of the rights and responsibilities of the public in advancing health through research and discovery. We argue that the public has the right not merely to participate in research and have their rights protected, but that they have a right to engage in and take ownership in research.